Gambaran sgot dan sgpt pada penderita penyakit tuberculosiS Paru (tb) dalam masa pengobatan 6 bulan di rumah sakit umum Wisata universitas indonesia timur - Andi Auliyah; Yuliana Puspita Sari (Jurnal Media Laboran, 2020)
The purpose of this study to determine the results of SGOT and SGPT examination in patients with pulmonary Tuberculosis and to determine the results of SGOT and SGPT levels can show improvement or not. The research was conducted by conducting observational research which analyzing the result of serum glutamic oxal-acetic transminase (SGOT) and serum glutamic pyruvic transminase (SGPT) examination on the patient of tuberculosis lung. The results showed that SGOT and SGPT levels were 70% normal because the patient’s immune system was in good condition and regular in taking anti tuberculosis drug (OAT), while the result of the abnormal SGOT and SGPT levels was 30% or the increase of SGOT and SGPT in patients this is because patients are less concerned or do not take anti tuberculosis drugs (OAT) according to a doctor’s prescription.